Antiviral treatment of childhood influenza: an update. Issue 3 (June 2018) - Moodley, Amaran; Bradley, John S.; Kimberlin, David W.
Abstract : Purpose of review: Influenza virus can cause severe or life-threatening infection in children. This review provides an update on antiviral medications available to treat and prevent influenza in both healthy children and children with underlying medical conditions, and recommendations on their appropriate use in the outpatient and inpatient settings. Recent findings: Despite the significant morbidity and mortality associated with influenza infection, a large number of children hospitalized with influenza do not receive specific antiviral treatment with a neuraminidase inhibitor. Although the effectiveness of this intervention has been debated, several recent observational studies have shown the potential benefits conferred by early antiviral treatment. Oral oseltamivir and inhaled zanamivir remain the best studied antiviral agents for influenza treatment and prevention. In addition, the US Food and Drug Administration recently approved peramivir, a novel neuraminidase inhibitor available for intravenous administration. Summary: Children with suspected or documented influenza infection benefit from early antiviral treatment with neuraminidase inhibitors that can shorten illness duration, decrease symptom severity, and lower the risk of complications leading to hospitalization and death. Unless contraindicated, all hospitalized children, children with underlying medical conditions, and those with severe or progressive symptoms of influenza should receive specific antiviral treatment for influenza with a neuraminidase inhibitor. Additionally, antiviral treatment of influenza-infected children in the outpatient setting should be strongly considered.